Bioefficacy of newer insecticides for the management of pod borer, Helicoverpa armigera of chickpea - Wadaskar, R M; Ughade, Jayashri; Patil, A N (Indian Journal of Plant Protection, 2017)
Gram pod borer, Helicoverpa armigera (Hubner) abundance throughout chickpea growth period especially in reproductive phase is the major bottleneck in attaining desired productivity levels of chickpea, the most importantnbRabi pulse crop of Maharashtra. The present study was designed to evaluate the efficacy of newer insecticides on pod borer and find out an effective and economical alternative to conventional insecticides for the ETL based management of pod borer. The evaluation categorically revealed superiority of flubendiamide 20 WDG @ 0.5 g/l, rynaxypyr 20 SC @ 0.25 ml/l, emamectin benzoate 5SG @ 0.3 g/l and spinosad 45 SC 0.3 ml/l in suppressing them population to the extent of 94.3-99.9 per cent over control, at 7 days and 14 days after application of insecticide. The higher efficacy of flubendiamide, rynaxypyr, emamectin benzoate and spinosad for pod borer suppression also translated into lower pod borer damage (1.6, 2.8, 3.0 and 3.3 per cent, respectively), higher yield (17.6, 16.6, 16.2 and 15.5 q/ha, respectively) and net profit of ` 14034, ` 10707, ` 9522 and ` 6974 per ha, respectively. ICBR analysis revealed application of emamectin benzoate as the most effective and economic treatment; application of flubendiamide and rynaxypyr can also be recommended for pod borer management in chickpea. Although, application of spinosad registered higher efficacy for pest management, on account of higher cost it had lowest ICBR ratio.